STUDI KOMPARATIF PENGGUNAAN MEDIA POP-UP BOOK DIGITAL CERITA “LEGENDA DANAU KERINCI: CALUNGGA DAN CALUPAT” DAN E-BOOK PADA SISWA SMP - Zelahayani; Yusra D; Rahmawati (STKIP Subang, 2026)
The development of digital technology has encouraged the use of more innovative learning media in Indonesian language learning at the Junior High School (SMP) level, especially in learning folklore that requires an understanding of the storyline, characters, and cultural values. This study aims to compare student learning outcomes between the use of E-Book media and digital Pop-Up Book media in learning the folklore